2022
DOI: 10.1021/acs.jced.2c00172
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Gasoline Using Deep Eutectic Solvents Based on Tetrabutylammonium Bromide

Abstract: The present study investigated the viability of deep eutectic solvents (DESs) to extract dibenzothiophene (DBT) from model gasoline (iso-octane). Tetrabutylammonium bromide (TBAB)-based DES showed significant DBT extraction capability from the model fuel oil. Furthermore, the sigma profile confirmed that all TBAB-based DES had a significant capacity for DBT extraction from the model oil. The affinity order for the TBABbased DES is as follows: TBAB/TEG (tri-ethylene glycol) > TBAB/PA (propionic acid) > TBAB/EG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Sulfur-containing hydrocarbons (Figure ) emit sulfur oxides (SO x ) during combustion, which harm human health and destroy the environment. Researchers have developed various desulfurization technologies, such as extraction, , adsorption, oxidation, and a combination of these methodologies to overcome the above-mentioned problems. …”
Section: Heterocyclic Compound Extraction Using Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur-containing hydrocarbons (Figure ) emit sulfur oxides (SO x ) during combustion, which harm human health and destroy the environment. Researchers have developed various desulfurization technologies, such as extraction, , adsorption, oxidation, and a combination of these methodologies to overcome the above-mentioned problems. …”
Section: Heterocyclic Compound Extraction Using Ilsmentioning
confidence: 99%
“…Studies on EDS using DESs as extractants indicate that the critical factors affecting the EDS performance are DES structures, the initial sulfur contents in oil, the DES/oil mass ratio, the degree of mutual solubility, temperature, extraction time, the number of extraction stages, etc. , The EDS performance is affected by HBA and HBD structures. Li et al .…”
Section: Relevant Extractive Separation With Il Analogs (Deep Eutecti...mentioning
confidence: 99%
“…10,11 However, in recent years, quaternary acid DESs have been widely used in areas such as separation and purification due to their simple, readily available, and low-cost raw materials. 12,13 Zuo et al 14 found that quaternary ammonium lactate-based DESs could efficiently remove N-compounds from simulated oils, but, no report on the physical properties of such DESs was available. It is known that the nature of a substance influences its use.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have recently developed various non-HDS methods to overcome these shortcomings, including adsorption desulfurization, 4 oxidative desulfurization, 5 membrane desulfurization, 6 biodesulfurization, 7 and extractive desulfurization. 8,9 Among these methods, extractive desulfurization has attracted widespread attention because of its low energy consumption, mild conditions, and simplicity.…”
Section: Introductionmentioning
confidence: 99%